Changes of oceanographic characteristics and the state of pollution in the Izmit bay following the earthquake of 1999 - (:unkn) unknown (SPRINGER, 2007)
The Izmit Bay is an elongated semi-enclosed bay in the Marmara Sea. It is being increasingly polluted by both domestic and industrial waste discharge since 1970's. A monitoring program was conducted between 1999-2000 to document the state of pollution in the bay. This includes the effect of Marmara (Izmit) earthquake (magnitude 7.4) that occurred in August 1999. A stable two-layer ecosystem exists in the bay throughout the year due to continuous inflows of the saltier Mediterranean and brackish Black Sea waters to the Marmara basin. Therefore, the principal biochemical characteristics of the bay are governed by the two-layer flow system over the basin. Dissolved oxygen (DO) is generally at a saturated levels in the surface layer which is 10 to 15 m thick, but it is depleted to 60-70 mu M in the lower layer, exhibiting a steep gradient in the sharp halocline. When the earthquake occurred, great loads of industrial wastes were released into the bay surface waters, which enhanced primary production in the upper layer and thus large export of particulate organic matter to lower layer and eventually to the bottom. Accordingly, DO was consumed and anoxic condition was established even in the upper layer/halocline interface, the halocline and bottom waters of the eastern and central bay. In this period, concurrent increases were observed in phosphate and ammonia contents at the halocline and in deep waters whilst the nitrate was almost consumed via denitrification processes in the anoxic water. Recently, the industrial C, N and P loads increased by as much as 8 fold within five years (1995-2000) whilst domestic inputs increased by 50%. Total organic matter discharged to the bay increased more than double within the last 15 years. Besides, most factories in the region release toxic wastes into the bay after only partial treatment.
Keywords: coastal contamination; water quality; oceanography; PHYTOPLANKTON; POLLUTANTS